IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING HORTATORY EXPOSITION TEXT THROUGH PLEASE STRATEGY - Marlin Sinambela; Johan Sinulingga (Universitas Negeri Medan, 2013)
This study attempts to improve students’ achievement in writing hortatory exposition text by using PLEASE (Pick, List, Evaluate, Activate, Supply, End) strategy through classroom action research. The subjects of the research were 41 students of class XI IA 2 SMA Negeri 1 Tanjung Morawa. After analyzing the data in the two-cycle of classroom action research, it was found that there was an improvement of students score from 49.88 in the test I became 64.90 in the test II in cycle I and improved again became 74.23 in the test III in cycle II. In line with the data, it was showed that the use of PLEASE (Pick, List, Evaluate, Activate, Supply, End) strategy significantly improved student’s achievement in writing hortatory exposition text. English teachers are suggested to apply PLEASE strategy as one of the alternatives to teach writing hortatory exposition text in the class. Keywords: Writing, Hortatory Exposition, Action research, PLEASE, SMA XI